Effectiveness of whey protein supplementation during resistance exercise training on skeletal muscle mass and strength in older people with sarcopenia: a systematic review and meta-analysis - Cuyul Vásquez, Iván.; Pezo Navarrete, José.; Vargas Arriagada, Cristina.; Ortega Díaz, Cynthia.; Sepúlveda Loyola, Walter Aquiles.; Massao Hirabara, Sandro.; Marzuca Nassr, Gabriel Nasri. (MDPI, 2023)
Objective: To determine the effectiveness of whey protein (WP) supplementation during resistance exercise training (RET) vs. RET with or without placebo supplementation on skeletal muscle mass, strength, and physical performance in older people with Sarcopenia. Methods: Electronic searches in the PubMed, Embase, Scopus, Web of Science, LILACS, SPORTDiscus, Epistemonikos, and CINAHL databases were performed until 20 January 2023. Randomized clinical trials conducted on sarcopenic adults aged 60 or older were included. The studies had to compare the effectiveness of the addition of supplements based on concentrated, isolated, or hydrolyzed whey protein during RET and compare it with RET with or without placebo supplementation on skeletal muscle mass and strength changes. The study selection process, data extraction, and risk of bias assessment were carried out by two independent reviewers. Results: Seven randomized clinical trials (591 participants) were included, and five of them provided data for quantitative synthesis. The overall pooled standardized mean difference (SMD) estimate showed a small effect size in favor of RET plus WP for skeletal muscle mass according to appendicular muscle index, with statistically significant differences compared with RET with or without the placebo group (SMD = 0.24; 95% CI, 0.05 to 0.42; p = 0.01; I2 = 0%, p = 0.42). The overall pooled mean difference (MD) estimate showed a significant difference of +2.31 kg (MD = 2.31 kg; 95% CI, 0.01 to 4.6; p = 0.05; I2 = 81%, p < 0.001) in handgrip strength in the RET plus WP group compared with the RET group with or without placebo. The narrative synthesis revealed discordance between the results of the studies on physical performance. Conclusions: WP supplementation during RET is more effective in increasing handgrip strength and skeletal muscle mass in older people with Sarcopenia compared with RET with or without placebo supplementation. However, the effect sizes were small, and the MD did not exceed the minimally important clinical difference. The quality of the evidence was low to very low according, to the GRADE approach. Further research is needed in this field.
Keywords: Sarcopenia; Elderly; Whey protein; Resistance exercise; Strength training